Rituximab monitoring and redosing in pediatric neuromyelitis optica spectrum disorder. Issue 1 (February 2016) - Nosadini, Margherita; Alper, Gulay; Riney, Catherine J.; Benson, Leslie A.; Mohammad, Shekeeb S.; Ramanathan, Sudarshini; Nolan, Melinda; Appleton, Richard; Leventer, Richard J.; Deiva, Kumaran; Brilot, Fabienne; Gorman, Mark P.; et al.
Abstract : Objective: To study rituximab in pediatric neuromyelitis optica (NMO)/NMO spectrum disorders (NMOSD) and the relationship between rituximab, B cell repopulation, and relapses in order to improve rituximab monitoring and redosing. Methods: Multicenter retrospective study of 16 children with NMO/NMOSD receiving ≥2 rituximab courses. According to CD19 counts, events during rituximab were categorized as "repopulation, " "depletion, " or "depletion failure" relapses (repopulation threshold CD19 ≥10 × 10 6 cells/L). Results: The 16 patients (14 girls; mean age 9.6 years, range 1.8–15.3) had a mean of 6.1 events (range 1–11) during a mean follow-up of 6.1 years (range 1.6–13.6) and received a total of 76 rituximab courses (mean 4.7, range 2–9) in 42.6-year cohort treatment. Before rituximab, 62.5% had received azathioprine, mycophenolate mofetil, or cyclophosphamide. Mean time from rituximab to last documented B cell depletion and first repopulation was 4.5 and 6.8 months, respectively, with large interpatient variability. Earliest repopulations occurred with the lowest doses. Significant reduction between pre- and post-rituximab annualized relapse rate (ARR) was observed ( p = 0.003). During rituximab, 6 patients were relapse-free, although 21 relapses occurred in 10 patients, including 13 "repopulation, " 3 "depletion, " and 4 "depletion failure" relapses. Of the 13 "repopulation" relapses, 4 had CD19 10–50 × 10 6 cells/L, 10 had inadequate monitoring (⩽1 CD19 in the 4 months before relapses), and 5 had delayed redosing after repopulation detection. Conclusion: Rituximab is effective in relapse prevention, but B cell repopulation creates a risk of relapse. Redosing before B cell repopulation could reduce the relapse risk further. Classification of evidence: This study provides Class IV evidence that rituximab significantly reduces ARR in pediatric NMO/NMOSD. This study also demonstrates a relationship between B cell repopulation and relapses.